Microbiology Profile in Women With Pelvic Inflammatory Disease in Relation to IUD Use. Issue 4 (2005) - Viberga, I.; Odlind, V.; Lazdane, G.; Kroica, J.; Berglund, L.; Olofsson, S.
Abstract : Objective. To study the microbial characteristics of patients with pelvic inflammatory disease (PID) and the possible impact of an intrauterine device (IUD) on the microbial environment in women presenting with PID. Methods. Case-control study, investigating 51 women with acute PID and 50 healthy women. Endocervical specimens for microbiological investigation were obtained at gynaecological examination. Results. IUD users with PID had significantly more Fusobacteria spp. and Peptostreptococcus spp. than non-IUD users with PID. The finding of combinations of several anaerobic or aerobic microbes was associated with a significantly increased risk of PID and with complicated PID. In IUD users, the combinations of several anaerobic/aerobic microbes were associated with an increased risk of PID, irrespective of duration of IUD use. Long-term IUD use appeared to be associated with an increased risk of a PID being complicated. Conclusion. The finding of several anaerobic or aerobic microbes appears to be associated with PID in users of IUD.